Guide to Collecting and Maintaining Live Arthropods for Classroom Display in Florida - S. McCann; James D. Ellis; Michael K. O'Malley (EDIS)
ENY-1001, a 6-page illustrated fact sheet by S. McCann, J. D. Ellis, and M. K. O’Malley, details the process of maintaining live insect displays for educational purposes in Florida. Includes references. Published by the UF Department of Entomology and Nematology, October 2008.